Kinetics of reductive alkylation of p-phenylenediamine with methyl ethyl ketone using 3% Pt/Al2O3 catalyst in a slurry reactor - Patil, Narendra G.; Roy, Debdut; Chaudhari, Amit S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Intrinsic kinetics of reductive alkylation of p-phenylenediamine (PPDA) with methyl ethyl ketone (MEK) using 3% Pt/Al2O3 catalyst was studied in a slurry reactor. The overall reaction involves a combination of parallel and consecutive reactions involving equilibrium noncatalytic (homogeneous) and catalytic (heterogeneous) steps. For the purpose of kinetic modeling, the effects of PPDA concentration, catalyst loading, agitation speed, and partial pressure of hydrogen were studied in a temperature range of 373-413 K. Quantitative criteria were used to ensure that the reaction occurred in the kinetic regime. Different rate equations have been considered based on the elementary steps involving catalytic and noncatalytic reactions, which lay stress on the different types of interactions occurring between the reactants and the active catalyst sites. The best-fit rate model has been proposed by rigorous optimization and model discrimination procedures, by simulating the experimental concentration-time data. For the best-fit model, the agreement between the predicted and experimental data was found to be very good over a wide range of operating conditions.

Immobilized palladium nanoparticles catalyzed oxidative carbonylation of amines - Didgikar, Mahesh R.; Roy, Debdut; Gupte, Sunil P.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2010)
Catalytic application of immobilized palladium nanoparticles for synthesis or ureas by oxidative carbonylation of amines has been investigated. This is the first report oil oxidative carbonylation of amines to ureas using immobilized palladium nanoparticles catalyst. The palladium nanoparticles were immobilized on a NaY zeolite support through 3-aminopropyl-trimethoxysilane (APTS) as anchoring agent. The [Pd]-APTS-Y catalyst along with NaI promoter showed high conversion and selectivity to the desired urea products over several amine compounds including ail example of an aliphatic amine precursor even at 333 K. The immobilized catalyst was easily separated and recycled several times without any loss of activity. The role of different solvents, iodide promoters, iodide to Pd ratio, concentration of substrates, and temperature on the overall yield of the reaction was also investigated.

Kinetics of reductive alkylations of phenylenediamines: influence of substrates isomeric structure - Roy, Debdut; Chaudhari, Amit S.; Chaudhari, Raghunath V. (Chemical Engineering Science, 2010)
Reductive alkylation of ortho-, meta- and para-phenylenediamines (PDAs) with methyl ethyl ketone (MEK) has been studied in a semi-batch slurry reactor in the presence of a commercial 3% Pt/Al(2)O(3) catalyst. It was observed that the PDA isomers differ remarkably from each other in their activity in reductive alkylation and product distribution. The activity was found to decrease in the following order: PPDA > OPDA > MPDA. To understand the substrate structure-activity correlation, the homogeneous equilibrium reactions involved in the alkylation step and the overall catalytic reactions were studied separately. Kinetics of reductive alkylation of PDAs with MEK as a solvent and alkylating agent with 3% Pt/Al(2)O(3) catalyst was studied in a semi-batch slurry reactor over a temperature range of 373-453K and pressure range of 2.07-6.21 MPa. Semi-batch slurry reactor models were developed and kinetic parameters were estimated by fitting the integral batch reactor data at different temperatures to understand the influence of different reaction steps on the activity and selectivity of different products. Published by Elsevier Ltd.
Keywords: Batch; catalysis; kinetics; Multiphase reactions; Phenylenediamines; Reaction engineering; Reductive alkylation